Leaching of nitrogen in barley, grass ley and fallow lysimeters - Yläranta, Toivo; Uusi-Kämppä, Jaana; Jaakkola, Antti (Agricultural and Food Science, 1993)
The leaching of nitrogen from fallow, fertilized and unfertilized spring barley, and grass ley was studied in a 4-year lysimeter experiment tcarried out on clay, silt and sand soils, and Carex peat. The experimental factors included also irrigation and treatments where the nitrogen fertilizer was applied in the first year as 15N-labelled ammonium nitrate. During four years, 41-66% of the nitrogen applied in the first growing season was recovered in plants harvested. Most of it, 91-96%, was taken up in the year applied. Mostly, the water drainage was lowest in silt and sand soils. The irrigation increased clearly the leaching of nitrogen almost in all treatments. Crops decreased the drainage of water through the lysimeters and the leaching of nitrogen, grass more than barley. The effects of plants and irrigation were similar in all soils, but most marked in sand. The largest amount of nitrogen was leached in irrigated, fallowed sand, 440 kg ha-1, during four years. The majority of the leached nitrogen was nitrate. Only in peat soil a significant amount of nitrogen was leached in some another form. The leaching of 15N-labelled fertilizer during four years was highest in sand, 2.3 kg ha 1 of N or 2.3% of the nitrogen applied in the first experimental year.